HUBUNGAN PENGGUNAAN GADGET TERHADAP PERKEMBANGAN ANAK DI PEKANBARU - Maya " "; Oswati " Hasanah; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Gadget is a electronic device that have a special function. Today we can see many children already have a gadget like smartphone or tablet. The use of  gadget can bring both positive and negative impact to children. Therefore, parents have very important roles in the use of gadget. The purpose of this research was to indentify correlation between use of gadget and children development at Pekanbaru. The type of this research was descriptive correlation with cross sectional approach. The respondents were parents and children in TK Pertiwi Pekanbaru. Sample was taken by purposive sampling technical with 194 respondents (97 parent’s & 97 children’s). Data taken by questionnaire about gadget and Denver Developmental Skrining Test II (DDST II) form. Data analysis by Chi-square test. The result were, 45 respondents use a gadget with positive effect, 32 respondents have normal development (71,1%), and 13 respondents have  suspected development (15,8%). Responden with negative effect were 52 children,which were 31 respondents have normal development (59,6%) and 21 respondents with suspected development (40,4%). chi square test found p value = 0,288  with  alpha = 0,05  (p value < alpha), it’s meant there is no correlation between gadget and children’s development at Pekanbaru. The results of this study can add into data or info about the relationship of use gadgets to children's development and to conduct further research on the characteristics of the elderly such as age, employment, education and others.  Keyword: DDST II, development , gadget